4 - Decentralising Natural Resource Management and the Politics of Institutional Resource Management in Uganda’s Forest Sub-Sector - Muhereza, Frank (Africa Development, 2006)
Since launching decentralisation in December 1992, Uganda has implemented wide-ranging public sector reforms as a part of broader democratisation, de- signed to ensure that powers over the management of public affairs are held by representative and downwardly accountable local authorities. This article ex- plores how these reforms have been implemented in Uganda’s forest sub-sec- tor. The forest-tenure regimes introduced under the 2003 National Forestry and Tree Planting Act have entrusted to various responsible bodies with the power to maintain, manage and control the different categories of forests. In actual practice, however, only limited powers have been effectively transferred away from the centre. Continued central control makes it extremely difficult to insu- late decision making over the allocation of licences from higher-level political pressures, since the ostensibly decentralised powers are exercised by actors who are upwardly accountable to these central forces. Forest sub-sector reform outcomes reveal that this upward accountability risks undermining popular participation and weakening democratic decision making. It also fetters the equity and efficiency potential of government poverty eradication programmes in the short and long term.